2003
DOI: 10.1016/s0042-6822(03)00294-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based, targeted deglycosylation of HIV-1 gp120 and effects on neutralization sensitivity and antibody recognition

Abstract: The human immunodeficiency virus (HIV-1) exterior envelope glycoprotein, gp120, mediates receptor binding and is the major target for neutralizing antibodies. Primary HIV-1 isolates are characteristically more resistant to broadly neutralizing antibodies, although the structural basis for this resistance remains obscure. Most broadly neutralizing antibodies are directed against functionally conserved gp120 regions involved in binding to either the primary virus receptor, CD4, or the viral coreceptor molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 63 publications
8
153
1
Order By: Relevance
“…Indeed, from the point of view of the Ag/Ab interaction, it has been shown that sugar moieties that apparently lie apart from the antibody's binding site can severely influence the access of the Ab to neutralizing epitopes (57). Thus, by analogy glycans present on the Fc region of F240 can dramatically affect the virus/Ab interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, from the point of view of the Ag/Ab interaction, it has been shown that sugar moieties that apparently lie apart from the antibody's binding site can severely influence the access of the Ab to neutralizing epitopes (57). Thus, by analogy glycans present on the Fc region of F240 can dramatically affect the virus/Ab interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glycans have been shown to play a vital role in various parasitic, bacterial, and viral disease infections [6]. For instance, interaction and fusion of the human immunodeficiency virus (HIV) with its target host cells is mediated by its envelope protein, gp160, which has over 50% of its mass comprising of glycans [7][8][9][10]. The high population and diverse range of glycans on this protein acts as a shield for the virus against the immune system; the glycans also mask epitopes that impact HIV disease progression [8,[11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…For instance, interaction and fusion of the human immunodeficiency virus (HIV) with its target host cells is mediated by its envelope protein, gp160, which has over 50% of its mass comprising of glycans [7][8][9][10]. The high population and diverse range of glycans on this protein acts as a shield for the virus against the immune system; the glycans also mask epitopes that impact HIV disease progression [8,[11][12][13][14][15][16][17]. Consequently, conducting glycoproteomics studies on this target, defining the structures and locations of glycans in the HIV envelope protein, is important in understanding how variation in glycosylation affects the functions of this protein, and the studies may also provide valuable information that can be useful in identifying new vaccine candidates.…”
mentioning
confidence: 99%
“…5, Table S2). Some studies reported that the loss of glycosylation in V3 affects the neutralization sensitivity of some HIV-1 strains (Koch et al, 2003;Li et al, 2008;Polzer et al, 2009;Wang et al, 2013). Recently, Zolla-Pazner et al (2015) proposed that the glycan on N301 restricts the mobility of the V3 loop.…”
Section: Discussionmentioning
confidence: 99%